AB0544 EVALUATION OF MACULAR AND OPTIC DISC MICROVASCULAR NETWORK IN PATIENTS WITH SYSTEMIC SCLEROSIS: AN OPTICAL COHORENCE TOMOGRAPHY ANGIOGRAPHY STUDY. (2nd June 2020) - Akay, F.; Akmaz, B.; Kabadayi, G.; Güven, Y. Z.; Solmaz, D.; Kurut Aysin, İ. and Gercik, O. and Akar, S.
Abstract : Background: Systemic sclerosis (SSc) is characterized by fibrosis of the skin, internal organs and vasculopathy. Invivo, the retina provides a unique opportunity to assess the microcirculation in the eye. Previous studies have been evaluated the changes in the retinal and choroid layer and showed thinning of the choroid layer and reduced retinal microvascular density. Objectives: To analysis the retinal and optic disc capillary network in patients with SSc without clinical signs of retinal involvement by using optical coherence tomography angiography (OCTA). Methods: In total 40 SSc patients who classified according to the ACR/EULAR criteria and 40 healthy control subjects were included in the analysis. All patients underwent a detailed ophthalmologic examination by the same ophthalmologist. After pupil dilatation, macular angiography was performed with 6x6 mm area scanning using standardized system and images of the retinal capillary plexus were analyzed by Cirrus OCTA software. Mean macular thickness, retinal nerve fiber layer (RNFL) and the Ganglion cell inner plexiform layer (GC-IPL), vessel density (VD), perfusion density (PD), optic disc PD, reflux index and foveal avascular zone (FAZ) parameters were measured by the same experienced operator. Results: There was no significant difference between SSc and controls in terms of age, sex, spherical equivalent (SE), intra ocular pressure (IOP), and axial length (AL). Central and mean macular thickness, nasal and inferior RNFL thicknesses were significantly thinner in SSc patients (Table). Additionally GC complex thicknesses were significantly thinner in all quadrants compared to controls. Central vessel density (CVD) and central perfusion density (CPD) values were found significantly decreased in all regions in patients with SSc. Optic disc perfusion density values were also decreased in SSc group. An inverse correlation was found between central macular thickness, FAZ area and perimeter values (rho:-0.300, p:0.007; rho:-0.276, p:0.013, respectively).There was no relationship between the disease duration and the OCTA measures. Conclusion: Vascular and perfusion density were found decreased in patient with SSC at the results of OCTA measures. These findings may help to understand vasculopathy in the pathogenesis of the disease and OCTA may be a new method providing objective and non-invasive information about capillary network in SSc. Disclosure of Interests: None declared